Pengaruh Model Pembelajaran Kooperatif Metode Mind mapping Terhadap Kemampuan Komunikasi Matematis - Siti Nur Afni Al Islami; Illah Winiati Triyana (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
In learning mathematics, mathematical communication skills play an important role because it allows students to express their mathematical thinking in writing. One of the approaches to improve this skill is through the application of cooperative learning that utilizes the mind mapping method. This study aims to assess the impact of cooperative learning model with mind mapping method on students' mathematical communication skills. The research method applied was quantitative with a quasi-experiment design. The population in this study were VIII grade students of Ma'arif Miftahul Ulum Junior High School in the even semester of the 2023/2024 academic year. The two classes involved in this study were class VIII A with 21 students and class VIII B with 20 students, which were used as research samples. Data collection techniques include mathematical communication ability tests and observations of the learning process whose results will be tested with statistical tests using SPSS 26.0. The results proved that there was a significant effect of using cooperative learning model with mind mapping method on students' mathematical communication skills, as seen from the hypothesis testing results with a significance value (2-tailed) of 0.051 > 0.05.